Toleransi Kedelai terhadap Tanah Salin - , Sunarto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2001)
Saline soil is widely distributed in Indonesia. This soil could inhibit and reduce growth and production. The aims of this research was to know the responce of several soybean varieties and lines to salinity. The result of this research showed that line name T22 was susceptible to saline soil. Mlg 2510 line was very tolerant to saline soil, and  on 0.4% salt concentration this line still produced seed.; Key words: Soybean, Saline soil.